1994
DOI: 10.1177/0265407594111001
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of Respect-Denying Behaviors among Male-Female Friendships

Abstract: The present study was designed to test the hypothesis that between-gender friendships are characterized primarily by behavioral exchanges involving respect but not affection (i.e. correlations between men's and women's behaviors would reach significance only for respect-related behavior). A total of 62 pairs of male-female pairs completed a 12-item version of the Role Behavior Test (Foa & Foa, 1974), designed to measure partners' frequency of affection-giving, affection-denying, respect-giving and respect-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…The patterns of resource exchange found among brother-sister pairs in the present study are highly similar to those found in a previous study of heterosexual dating cou-ples (Gaines, 1996, Study l), among whom affection-giving, respect-giving, and affection-denying behaviors were exchanged at significant levels. In contrast, the patterns of resource exchange found among brothersister pairs was highly dissimilar to those found in a previous study of male-female friendships (Gaines, 1994), among whom exchanges were limited to respect-denying behaviors; no such exchanges were evident in the present study of brother-sister pairs. Given that the literature on peer relationship processes typically emphasizes similarities between sibling relationships and friendships (von Salisch, 1997; see also Wish et al, 1976), the results of the present study may seem counterintuitive.…”
Section: Interpersonal Resource Exchange Among Brother-sister Relatiocontrasting
confidence: 99%
See 3 more Smart Citations
“…The patterns of resource exchange found among brother-sister pairs in the present study are highly similar to those found in a previous study of heterosexual dating cou-ples (Gaines, 1996, Study l), among whom affection-giving, respect-giving, and affection-denying behaviors were exchanged at significant levels. In contrast, the patterns of resource exchange found among brothersister pairs was highly dissimilar to those found in a previous study of male-female friendships (Gaines, 1994), among whom exchanges were limited to respect-denying behaviors; no such exchanges were evident in the present study of brother-sister pairs. Given that the literature on peer relationship processes typically emphasizes similarities between sibling relationships and friendships (von Salisch, 1997; see also Wish et al, 1976), the results of the present study may seem counterintuitive.…”
Section: Interpersonal Resource Exchange Among Brother-sister Relatiocontrasting
confidence: 99%
“…We adopted conservative criteria for evaluating canonical correlation results: First, we required statistical significance at the multivariate level prior to inspecting canonical coefficients. Second, we limited our attention to those pairs of canonical coefficients for which (a) the valences were of the same sign and (b) the magnitudes were .20 or greater (see also Gaines, 1994).…”
Section: Covariance Between Brothers' and Sisters' Giving Of Interpermentioning
confidence: 99%
See 2 more Smart Citations
“…So it is a natural topic with which to begin this section. Gaines (1994) was one of the first social science scholars to study respect explicitly within friendship and romantic pairs. He examined respect-giving and respect-denying behaviors along with affection behaviors in both same-sex and cross-sex friendships.…”
Section: Respect In Dyadsmentioning
confidence: 99%